A 3D Framework with Li3N–Li2S Solid Electrolyte Interphase and Fast Ion Transfer Channels for a Stabilized Lithium‐Metal Anode. Issue 8 (23rd December 2022) - Ni, Shuyan; Zhang, Mengtian; Li, Chuang; Gao, Runhua; Sheng, Jinzhi; Wu, Xin; Zhou, Guangmin
Abstract: The Li‐metal anode has been recognized as the most promising anode for its high theoretical capacity and low reduction potential. However, the major drawbacks of Li metal, such as high reactivity and large volume expansion, can lead to dendrite growth and solid electrolyte interface (SEI) fracture. An in situ artificial inorganic SEI layer, consisting of lithium nitride and lithium sulfide, is herein reported to address the dendrite growth issues. Porous graphene oxide films are doped with sulfur and nitrogen (denoted as SNGO) to work as an effective lithium host. The SNGO film enables the in situ formation of an inorganic‐rich SEI layer, which facilitates the transport of Li‐ions, improves SEI mechanical strength, and avoids SEI fracture. In addition, COMSOL simulation results reveal that the microchannels fabricated by the 3D printing technique further shorten the Li‐ion transfer pathways and homogenize heat and stress distribution in the batteries. As a result, the assembled anode shows low capacity fading of 0.1% per cycle at 2 C rate with the sulfur cathode. In addition, the high lithium utilization of the SNGO host enables the anode to provide a stable capacity at low negative/positive electrode ratios under 3 in LiS batteries. Abstract : An in situ artificial inorganic solid electrolyte interface layer is designed, consisting of lithium nitride and lithium sulfide, to provide fast Li‐ion kinetics and high mechanical strength. In addition, the graphene oxide host is constructed with evenly spaced microchannels to address the volume change and dendrite growth issues.